2018
DOI: 10.1002/elps.201800012
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective capillary electrophoresis provides insight into the phase II metabolism of ketamine and its metabolites in vivo and in vitro

Abstract: Glucuronidation catalyzed by uridine-5'-diphospho-glucuronosyl-transferases (UGTs) is the most important reaction in phase II metabolism of drugs and other compounds. O-glucuronidation is more common than N-glucuronidation. The anesthetic, analgesic and antidepressive drug ketamine is metabolized in phase I by cytochrome P450 enzymes to norketamine, hydroxynorketamine (HNK) diastereomers and dehydronorketamine (DHNK). Equine urine samples collected two hours after ketamine injection were treated with β-glucuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…HNKs undergo glucuronide conjugation, which is catalyzed at least partly by the uridine 5’-diphospho(UDP)-glucuronosyltransferase UGT2B4 (Moaddel et al, 2010). HNKs are eliminated both in their conjugated and unconjugated forms in urine and bile (Chang and Glazko, 1974; Dinis-Oliveira, 2017; Lankveld et al, 2006; Moaddel et al, 2010; Sandbaumhuter and Thormann, 2018; Turfus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HNKs undergo glucuronide conjugation, which is catalyzed at least partly by the uridine 5’-diphospho(UDP)-glucuronosyltransferase UGT2B4 (Moaddel et al, 2010). HNKs are eliminated both in their conjugated and unconjugated forms in urine and bile (Chang and Glazko, 1974; Dinis-Oliveira, 2017; Lankveld et al, 2006; Moaddel et al, 2010; Sandbaumhuter and Thormann, 2018; Turfus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HNKs undergo glucuronide conjugation, at least partly catalyzed by the UDP-glucuronosyltransferase isoform UGT2B4 (Moaddel et al, 2010), and are eliminated both in their unconjugated and conjugated forms in urine and bile (Chang and Glazko, 1974;Lankveld et al, 2006;Turfus et al, 2009;Moaddel et al, 2010;Dinis-Oliveira, 2017;Sandbaumhüter and Thormann, 2018). In mice, HNKs are detected up to 2-4 hours in the plasma and brain after intraperitoneal ketamine administration (Zanos et al, 2016(Zanos et al, , 2019a.…”
Section: Hydroxynorketamines Pharmacologymentioning
confidence: 99%
“…It was clearly shown that hydroxylated metabolites other than 6‐hydroxynorketamine were formed in the in vitro incubations and could also be detected in the plasma samples. In a subsequent study, the dual selector system was applied in combination with further methods, i.e., 2% (m/v) HS‐γ‐CD in a 17.8 mM Tris‐phosphoric acid buffer, pH 2.0, under reversed polarity of the applied voltage and 0.66% (m/v) HS‐γ‐CD in 100 mM sodium phosphate buffer, pH 3.0, in order to separate all metabolites in equine urine and to exclude interferences by endogenous compounds [141]. Furthermore, the samples were analyzed before and after treatment with β‐glucuronidase and arylsulfates to conclude on the phase‐II metabolism of the drug.…”
Section: Ce In Stereoisomer Analysis Of Pharmaceuticalsmentioning
confidence: 99%